Toxicity of building materials - Torgal, Fernando Pacheco; Jalali, Said, 1946-; Fucic, A. (Aleksandra) (Cambridge, UK ; Philadelphia, PA : Woodhead Pub., 2012)
From long-standing worries regarding the use of lead and asbestos to recent research into carcinogenic issues related to the use of plastics in construction, there is growing concern regarding the potential toxic effects of building materials on health. Toxicity of building materials provides an essential guide to this important problem and its solutions. Beginning with an overview of the material types and potential health hazards presented by building materials, the book goes on to consider key plastic materials. Materials responsible for formaldehyde and volatile organic compound emissions, as well as semi-volatile organic compounds, are then explored in depth, before a review of wood preservatives and mineral fibre-based building materials. Issues related to the use of radioactive materials and materials that release toxic fumes during burning are the focus of subsequent chapters, followed by discussion of the range of heavy metals, materials prone to mould growth, and antimicrobials. Finally, Toxicity of building materials concludes by considering the potential hazards posed by waste based/recycled building materials, and the toxicity of nanoparticles. With its distinguished editors and international team of expert contributors, Toxicity of building materials is an invaluable tool for all civil engineers, materials researchers, scientists and educators working in the field of building materials. Provides an essential guide to the potential toxic effects of building materials on healthComprehensively examines materials responsible for formaldehyde and volatile organic compound emissions, as well as semi-volatile organic compoundsLater chapters focus on issues surrounding the use of radioactive materials and materials that release toxic fumes during burning.
7 Mineral fibre-based building materials and their health hazards7.1 Introduction; 7.2 Classification of asbestos and mineral fibres, their structure, microstructure and properties; 7.3 Health effects of asbestos minerals; 7.4 Use of asbestos in building materials; 7.5 The reclamation of asbestos; 7.6 The disposal of asbestos-containing materials (ACMs) and recycling; 7.7 Conclusion and future trends; 7.8 Sources of further information and advice; 7.9 References; 8 Radioactive materials; 8.1 Introduction; 8.2 Naturally occurring radioactive materials (NORM).
Includes bibliographical references and index.
Keywords: Building materials -- Toxicology; Building materials -- Environmental aspects; Hazardous substances; TECHNOLOGY & ENGINEERING -- Construction -- General; Building materials -- Environmental aspects; Building materials -- Toxicology; Hazardous substances